THE USE OF BROCCOLI AND BROCCOLI SPROUTS IN THE PREVENTION ANDTREATMENT OF VARIOUS DISEASES (American Journal of Research in Humanities and Social Sciences, 2025)
All over the world preference is given to natural plant products, as medicines and vegetables for the prevention and treatment of various diseases. Epidemiological studies have shown that natural foods strengthen the immune system and act asanti-inflammatory, antioxidant, anti-mutagenic and anti-cancer agents. One of such agents is the miraculous vegetable broccoli and broccoli sprouts from the Brassicaceae family.